2006
DOI: 10.2174/157015906776359577
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Cell Death in Alzheimers Disease and a Neuroprotective Factor, Humanin

Abstract: Brain atrophy caused by neuronal loss is a prominent pathological feature of Alzheimer's disease (AD). Amyloid beta (Abeta), the major component of senile plaques, is considered to play a central role in neuronal cell death. In addition to removal of the toxic Abeta, direct suppression of neuronal loss is an essential part of AD treatment; however, no such neuroprotective therapies have been developed. Excess amount of Abeta evokes multiple cytotoxic mechanisms, involving increase of the intracellular Ca(2+) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 93 publications
(150 reference statements)
5
90
0
Order By: Relevance
“…An attempt was made to directly dissolve the peptide at 2 mg/ml with PBS, which generated visible particulates and precipitates. It is evident that these peptides must be first dissolved in water, not PBS or other solvents, for high solubility, as has been done [1][2][3][4][5][6]. Thus, CD analysis was done using the stock solution of AGA-(C8R)HNG17 first dissolved in water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An attempt was made to directly dissolve the peptide at 2 mg/ml with PBS, which generated visible particulates and precipitates. It is evident that these peptides must be first dissolved in water, not PBS or other solvents, for high solubility, as has been done [1][2][3][4][5][6]. Thus, CD analysis was done using the stock solution of AGA-(C8R)HNG17 first dissolved in water.…”
Section: Resultsmentioning
confidence: 99%
“…A 24-amino acid peptide, Humanin (HN), is a novel peptide that protects neuronal cells in vitro and in vivo from neurotoxic insults involved in Alzheimer's diseases [1][2][3][4][5][6][7]. During structure-activity analysis, a single mutation in HN of Ser14 to Gly (HNG) was found to increase the activity 1000-fold [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was originally found in the occipital lobe of an autopsied Alzheimer's disease (AD) patient [13][14][15]. Multiple studies demonstrated that humanin suppresses neuronal cell death caused by AD-specific insults, including both amyloid-beta (Abeta) peptides and familial AD-causative genes [26,31], by binding to a novel IL-6-receptor-related receptor(s) on the cell surface involving CNTFRalpha (ciliary neurotrophic factor receptor alpha), WSX-1 (IL-27 receptor subunit), and gp130 [16,28], and by preventing mitochondrial dysfunction [20]. This endogenous peptide can also activate the JAK2/ STAT3 signaling axis, triggering a signal transduction cascade linked to the inhibition of AD-related neurotoxicity [5].…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that CPE is required for the sorting and processing of proteins and peptides that promote cell survival such as activitydependent neuroprotective protein (ADNP; Gozes 2007), humanin, a peptide which suppresses cell death induced by Alzheimer's disease-related insults in vitro (Niikura et al 2006) and BDNF which may be attenuated in some neurodegenerative diseases, such as Alzheimer's disease, Parkinson's disease, and Huntington's disease (Chao et al 2006;Zuccato and Cattaneo 2007).…”
mentioning
confidence: 99%